Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1177/107110070102200312
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adult Acquired Flatfoot Deformity on Tibiotalar Joint Contact Characteristics

Abstract: Changes in the tibiotalar contact characteristics were investigated using eight fresh frozen cadaver ankle specimens to further develop an established model of the acquired flatfoot deformity. The deformity was simulated by sectioning the tendons and ligaments of the ankle and foot that normally support the longitudinal arch. Axial loads of 1,350 N were applied to the foot in a neutral position in both the intact specimen and flatfoot model. The flatfoot condition resulted in significant lateral shifts of 5.28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…For the contact at the tibiotalar joint, many experimental studies have been reported in the literature (Beaudoin et al, 1991;Bertsch et al, 2001;Calhoun et al, 1994;Clarke et al, 1991;Curtis et al, 1992;Driscoll et al, 1994;Earll et al, 1996;Friedman et al, 2001;Hartford et al, 1995;Kimizuka et al, 1980;Macko et al, 1991;Michelson et al, 2001;Pereira et al, 1996;Ramsey and Hamilton, 1976;Steffensmeier et al, 1996;Tarr et al, 1985;Thordarson et al, 1997;Ting et al, 1987), particularly looking at the effect of joint flexion position, joint loading, and integrity of the ligaments. Most of these are limited by the invasive measuring devices, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…For the contact at the tibiotalar joint, many experimental studies have been reported in the literature (Beaudoin et al, 1991;Bertsch et al, 2001;Calhoun et al, 1994;Clarke et al, 1991;Curtis et al, 1992;Driscoll et al, 1994;Earll et al, 1996;Friedman et al, 2001;Hartford et al, 1995;Kimizuka et al, 1980;Macko et al, 1991;Michelson et al, 2001;Pereira et al, 1996;Ramsey and Hamilton, 1976;Steffensmeier et al, 1996;Tarr et al, 1985;Thordarson et al, 1997;Ting et al, 1987), particularly looking at the effect of joint flexion position, joint loading, and integrity of the ligaments. Most of these are limited by the invasive measuring devices, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, many cadaveric models utilize substantial sectioning of ligaments and tendons to create the deformity. 6,14,15,[17][18][19] Sectioning simulates complete rupture, which does not typically occur in vivo. 20 Attenuation of ligaments and tendons followed by cyclic axial loading has been used to simulate progressive development of soft tissue laxity.…”
mentioning
confidence: 99%
“…These results support the hypothesis of lateral shift of the intra-articular pressure distribution in a cadaveric flat foot model during midstance. Previous studies reported a lateral localization of both global contact area and peak pressure on the talar dome in a cadaveric flat foot model when compared to the intact specimens (Friedman et al, 2001;Havenhill et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Few previous studies described the effects of a flatfoot deformity on tibiotalar joint contact characteristics (Havenhill et al, 2005;Friedman et al, 2001). The lateral load shift which was described in flat feet may be responsible for degenerative changes in long-lasting deformities (Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 97%